2022
DOI: 10.11646/zootaxa.5214.4.5
|View full text |Cite
|
Sign up to set email alerts
|

A new species of scleractinian associated shrimp of the genus Palaemonella (Crustacea, Decapoda, Palaemonidae) with a redescription of Palaemonella orientalis Dana, 1852

Abstract: A new species of Palaemonella, P. rubrolineata sp. nov., is described on the basis of material collected from pocilloporid corals in Indonesia and Vanuatu. The new species is most closely related to P. orientalis, another tropical Indo-West Pacific species usually found in association with pocilloporid and acroporid corals. The new species can be distinguished from P. orientalis based on the presence of a hepatic spine, the more slender rostrum, body and longer appendages, the pleura of the fifth abdominal seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, so‐called ‘inquilinistic or inquiline forms’ of palaemonid shrimps have evolved to share a burrow with pistol shrimps (Caridea: Alpheidae), opisthognath fish or echiurids (Frolová et al., 2022 ). This above‐mentioned host range is presumably an incomplete record, as many other symbiotic interactions have not been identified yet, and more associations are still being discovered (Anker & De Grave, 2021 ; de Gier & Fransen, 2018 ; Fransen et al., 2021 , 2022 ; Komai et al., 2023 ; Rauch et al., 2019 ). Several studies have demonstrated interphylum host switching to be important in the past diversification of the family (Davis et al., 2018 ; Gan et al., 2015 ; Horká et al., 2016 , 2018 ; Kou et al., 2013 , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, so‐called ‘inquilinistic or inquiline forms’ of palaemonid shrimps have evolved to share a burrow with pistol shrimps (Caridea: Alpheidae), opisthognath fish or echiurids (Frolová et al., 2022 ). This above‐mentioned host range is presumably an incomplete record, as many other symbiotic interactions have not been identified yet, and more associations are still being discovered (Anker & De Grave, 2021 ; de Gier & Fransen, 2018 ; Fransen et al., 2021 , 2022 ; Komai et al., 2023 ; Rauch et al., 2019 ). Several studies have demonstrated interphylum host switching to be important in the past diversification of the family (Davis et al., 2018 ; Gan et al., 2015 ; Horká et al., 2016 , 2018 ; Kou et al., 2013 , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…As is the case for most taxonomy-based studies, the work never appears to be finished. New symbiotic species of palaemonid shrimps and pinnotherid crabs continue to be discovered, sometimes found in remote places, in elusive host organisms, or in a museum collection (Chapter 3;Fransen et al, 2022Neves, 2022;. Hopefully, the phylogenetic and morphometric methods from this thesis will be used to include additional species, or they can be applied in different biological fields.…”
Section: Concluding Wordsmentioning
confidence: 99%
“…The Pontoniinae, however, were made up of almost exclusively much-smaller marine endo-and ectosymbionts (De Grave & Fransen, 2011). Now, estimates 1 of the fraction of symbiotic species among the marine Palaemonidae reaches up to 70% (Chow et al, 2022), with additional species being discovered every year (Fransen et al, 2022;Neves, 2022;. This group is now colloquially called the group of the 'commensal shrimps'.…”
Section: Commensal Shrimpmentioning
confidence: 99%
See 1 more Smart Citation